USING JARGONS AND SLANGS IN FORMAL SPEECH PROCESS (ON EXAMPLE PROGRAM OF TV, MEETING) - Pulatova Sevinch; Nurmukhammedova Nilufar; Aminova Sohila (World Scientific Research Journal, 2025)
Abstract: Jargons and slangs are often used in informal communication. However, in nowadays they are also used in formal style. This article was analyzed the positive and negative aspects of using jargon and slang in formal speech. It mainly studies how slang and jargon words are perceived by audiences and their impact on communication effectiveness, mainly in television and official meetings. The article discusses how jargons and slangs can cause confusion or ambiguity for listeners.